Exploiting spinel manganese oxide decorated with silver nanoparticles as electrodes for supercapacitor application - Monika Michalska; Martin Sarman; Janhavi Sharma; Chandini Kumar; Kamil Sobczak; Pramod Kumar Singh; Amrita Jain (Scientific Reports)
Abstract This work presents a novel approach to the development of supercapacitor technology through the integration of a gel polymer electrolyte (GPE) and Ag nanoparticle (NP) modified Mn3O4 electrodes. To the best of our knowledge, this is the first study to employ a GPE comprising poly(vinylidene fluoride)-co-hexafluoropropylene (PVdF-HFP) as the host polymer, propylene carbonate (PC) as the plasticizer, and magnesium perchlorate (Mg(ClO4)2) as the salt, in conjunction with Ag NP-modified Mn3O4 electrodes. The study also introduces a pioneering low-temperature ultrasonication method for the attachment of Ag NPs to Mn3O4, which eliminates the need for a reducing agent. This approach is characterized by its simplicity, cost-effectiveness, and scalability, offering significant advantages over conventional methods. The electrochemical performance of the resulting supercapacitor cells, featuring the modified electrodes and novel GPE, was comprehensively evaluated, yielding a single electrode specific capacitance of 9.38 F g⁻¹, with an energy density of 1.9 Wh kg⁻¹, and a power density of 30.8 W kg⁻¹. The findings demonstrate the potential of this new system to enhance energy storage capabilities, marking a substantial advancement in supercapacitor research, and this study sets the foundation for future investigations into scalable, high-performance energy storage solutions, emphasizing both innovation in material design and process optimization.